The Rest of the Dream : The Black Odyssey of Lyman Johnson - Johnson, Lyman T., 1906-1997 (Book collections on Project MUSE., 1988)
In The Rest of the Dream, Lyman Johnson, grassroots civil rights leader, tells his own story. All four of Johnson's grandparents were slaves in Tennessee. Yet his father was a college graduate, principal of a black school, and the inspiration for his son's love of justice. Lyman Johnson was born in 1906 during the darkest days of segregation. He learned from his father not to sit in the ""crow's nest"" reserved for blacks in his hometown movie theater. This refusal to accept second-class citizenship became a guiding principle in Johnson's life. Johnson was almost forty-three when he won admis